Penerapan metode latihan terbimbing dalam pembelajaran tenis meja untuk meningkatkan hasil belajar Mahasiswa - Solissa, Jonas (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to improve student learning outcomes in table tennis courses through guided training methods. The research was carried out on students of Physical Education, Health and Recreation at Pattimura University for the 2022/2023 Academic Year. Using the type of Classroom Action Research (Classroom Action Research). The instruments used for data collection are observation and performance tests of forehand and backhand hitting skills in table tennis (Assessment Rubric). Based on the results of this study, it shows that the application of guided training methods in table tennis learning on the subject of basic techniques of forehand and backhand strokes has a positive impact on improving student learning outcomes, this can be seen from the absorption of students increasing from the first cycle by 65.74% (12 students out of 34 students have completed learning) and the second cycle increasing to 82.79%. In the second cycle, the completeness of student learning has been classically achieved. This means that it has achieved the success indicators as expected by researchers and lecturers of the Table Tennis course.